Sweet Heart Sdn. Bhd. / Amy Michelle Segi … [et al.] - Segi, Amy Michelle; Morris, Deborah; Minggan, Jackson Jalie; Atopia, Sherine; Nyarep, Nasheda Alencia (2018)
Sweet Heart Sdn. Bhd. has been established for nine years which in around 2008 or 2009. Sweet Heart Sdn.Bhd. has several branches around Sarawak but we choose the branch that is located in 47 49, Phase 25, Jalan Datuk Mohd Musa, Desa Ilmu,94300 Kota Samarahan ,Sarawak. Sweet Heart Sdn.Bhd. is founded by Sim Kiap Sian with his brothers Sim Kwang Sian and Sim Chiew Sian. Sweet Heart Sdn.Bhd. practice partnership business since the business has been established. For the organizational structure, the Sweet Heart Sdn.Bhd. is headed by Sim Sian Kiap and his brothers and under them is consists of their workers which are supervisors and ordinary workers. They have variety of products that they sell in their premise such as snacks, beverages, beans, nuts and they as well sells items such as food containers ,cups and straws. The services that they provided are delivery service as well as cash-on-delivery. For their financial achievement, the Sweet Heart Sdn.Bhd. has been gaining their profit before tax 20,000 monthly and their profit increases 5% per year since they have been established. Sweet Heart Sdn.Bhd faced few business problems such as lack of employees at their premise and their items are not well organize. We suggested some solution to tackle this problems and they are advertising vacancy through social media, consider offering raises and consider hiring more workers. We also recommended Sweet Heart Sdn.Bhd to widen their publicity since they lacking in publicity marketing and doing online marketing strategies.